EXPLORING THE IMPORTANCE OF DEVELOPING READING SKILL IN THE MODERN ENGLISH CLASSROOMS - Zhantleyeva, М. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
One of the most important components of the process of teaching English language at all levels is building learners’ reading competence. Reading is one of the most important aspects of communicative and cognitive activity of students that is reached information from a written fixed text by using critical thinking instruments. For the current stage of development of linguistics there is sufficiently extensive theoretical material on how to form and improve readers’ skills in an English classroom setting and it discussed and reviewed by many researchers. Training is defined as a form of communication, refers to the field of speech activity of people, is realized in the form of indirect speech telecommunications. Reading also determines the written form of communication. Intermediate and directed communication process. Extracting information from written text. There are two things to keep in mind when learning to read. Its components are reading methods and reading comprehension. The work addresses the interrelationship and interdependence of these two aspects that contribute to this overarching goal. The type of speech, especially the understanding of written speech and its relation to it.
Keywords: training; type of oral activity; "technical" aspect; verbal communication; reading comprehension; communication skills in a foreign language